Analisis Program Bimbingan Perkawinan dalam Mewujudkan Keluarga Sakinah untuk Membangun Karakter Bangsa - Putra, Gusti (JURNAL ILMIAH GEMA PERENCANA, 2023)
The effectiveness of premarital marriage guidance can be seen from: 1) the precise formulation of the guidance objectives, 2) the quality of the guidance process, 3) the level of readiness for marriage after following the guidance. Subjects in the study, out of 60 prospective brides, 40 prospective brides were taken as research samples who had taken premarital marriage guidance Batch I of 2020 at the Office of Religious Affairs (KUA) of West Pontianak District, Pontianak City. Data collection techniques used in research is by using questionnaires / questionnaires. The results of this study found: 1) the guidance of the bride and groom resulted in an accuracy rate of 18.23%. This implies that the purpose of premarital guidance has a compatibility level that has less good relevance compared to the bride/groom's actual information needs; 2) the guidance process produces a quality level value of 70%. This shows that the quality of the guidance process has led to better things to achieve the goals of marriage guidance;